2017
DOI: 10.1016/j.exger.2017.02.075
|View full text |Cite
|
Sign up to set email alerts
|

Epigallocatechin-3-gallate increases autophagy signaling in resting and unloaded plantaris muscles but selectively suppresses autophagy protein abundance in reloaded muscles of aged rats

Abstract: We have previously found that Epigallocatechin-3-gallate (EGCg), an abundant catechin in green tea, reduced apoptotic signaling and improved muscle recovery in response to reloading after hindlimb suspension (HS). In this study, we investigated if EGCg altered autophagy signaling in skeletal muscle of old rats in response to HS or reloading after HS. Fischer 344 x Brown Norway inbred rats (age 34 mo.) were given 1 ml/day of purified EGCg (50 mg/kg body weight), or the same sample volume of the vehicle by gavag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
2
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 94 publications
(137 reference statements)
1
32
2
1
Order By: Relevance
“…We showed an acute but transient increase in the autophagosome formation markers Map1lc3b-I, Gabarapl1, and Sqstm1 protein, and a decrease and subsequent increase in the Map1lc3b-II:I ratio that parallels the regulation of late stages of myogenesis. In line with our data, previous studies showed an increase in Sqstm1 protein expression (27) and an increase in Map1lc3b-II:I ratio (31). In addition, White et al (63) reported an unaltered Map1lc3b-II:I ratio after 14 d of RL, potentially reflecting a normalization of autophagy signaling upon completed recovery.…”
Section: Discussionsupporting
confidence: 91%
“…We showed an acute but transient increase in the autophagosome formation markers Map1lc3b-I, Gabarapl1, and Sqstm1 protein, and a decrease and subsequent increase in the Map1lc3b-II:I ratio that parallels the regulation of late stages of myogenesis. In line with our data, previous studies showed an increase in Sqstm1 protein expression (27) and an increase in Map1lc3b-II:I ratio (31). In addition, White et al (63) reported an unaltered Map1lc3b-II:I ratio after 14 d of RL, potentially reflecting a normalization of autophagy signaling upon completed recovery.…”
Section: Discussionsupporting
confidence: 91%
“…Skeletal muscle lysates were analysed with Western immunoblots as previously described, with slight modifications. Sodium dodecyl sulfate‐polyacrylamide gel electrophoresis was run on 4–12% gradient NuPAGE Bis‐Tris gels (ThermoFisher Scientific, Pittsburgh PA, USA) at 120 V for 2 h in NuPAGE MES SDS buffer (ThermoFisher Scientific, Pittsburgh PA, USA).…”
Section: Methodsmentioning
confidence: 78%
“…Protein concentrations of samples were determined by the Lowry method, and the purity of each fraction was confirmed as reported previously . Forty micrograms of protein were loaded into each well of a 4–12% gradient polyacrylamide gel (Invitrogen, Carlsbad, CA) and separated by routine sodium dodecyl sulfate‐polyacrylamide gel electrophoresis for 1 h at 120 V. The proteins were transferred to a nitrocellulose membrane for 1.5 h at 25 V. Non‐specific protein binding was blocked by incubating the membranes in 5% nonfat milk in Tris‐buffered saline containing 0.05% Tween 20 …”
Section: Methodsmentioning
confidence: 99%
“…Herein, we discuss animal models that have been used to study sarcopenia based on the molecular mechanisms of each model (Table 2). [150][151][152] Animal models of sarcopenia with chronic diseases (e.g., cancer cachexia, chronic pulmonary diseases) are not included, we summarize animal models that have been widely used as in vivo models associated sarcopenia. ↑; increase, ↓; decrease, ↔; no change.…”
Section: Animal Modelsmentioning
confidence: 99%
“…The elevated animal's hindlimbs are adjusted and suspended from the ground, while the forelimbs remain free [149]. HLS can contribute to muscle atrophy by disrupting several cellular processes such as inducing oxidative imbalance [149], mitochondrial dysfunction [163], autophagy [150], and improper protein synthesis/degradation [164]. Hindlimb unloading disrupts the redox balance by inducing oxidative stress and decreasing antioxidant production (e.g., catalase and glutathione peroxidase) [149,165].…”
Section: Hindlimb Suspension (Microgravity)mentioning
confidence: 99%